2017
DOI: 10.1016/s1473-3099(16)30326-7
|View full text |Cite
|
Sign up to set email alerts
|

The geography of imported malaria to non-endemic countries: a meta-analysis of nationally reported statistics

Abstract: SummaryBackgroundMalaria remains a problem for many countries classified as malaria free through cases imported from endemic regions. Imported cases to non-endemic countries often result in delays in diagnosis, are expensive to treat, and can sometimes cause secondary local transmission. The movement of malaria in endemic countries has also contributed to the spread of drug resistance and threatens long-term eradication goals. Here we focused on quantifying the international movements of malaria to improve our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
159
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(168 citation statements)
references
References 39 publications
4
159
1
4
Order By: Relevance
“…An analysis of the GeoSentinel global surveillance network, which monitors travel-related illness, showed that 83% of travelers who contracted malaria were exposed in sub-Saharan Africa ( 56 ). Likewise, a meta-analysis with data from 2005–2015 showed that among imported malaria infections in 40 countries where malaria is not endemic, 56% of cases were from West Africa ( 57 ). …”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the GeoSentinel global surveillance network, which monitors travel-related illness, showed that 83% of travelers who contracted malaria were exposed in sub-Saharan Africa ( 56 ). Likewise, a meta-analysis with data from 2005–2015 showed that among imported malaria infections in 40 countries where malaria is not endemic, 56% of cases were from West Africa ( 57 ). …”
Section: Discussionmentioning
confidence: 99%
“…Although malaria is a mosquito-borne disease, human travel-mediated transmission on spatial scales that exceed the limits of mosquito dispersal has been undermining the success of malaria control and elimination programmes that have been implemented in many countries. [10][11][12]68 The early detection and treatment of imported parasites due to human travel become high priorities for informing malaria elimination policy. A variety of models, integrating CDR-derived human mobility and malaria epidemiological and entomological data, have investigated the dynamics of human carriers to identify importation routes and locate transmission foci that contribute to malaria epidemiology for endemic countries in sub-Saharan Africa, Mesoamerica and South-East Asia.…”
Section: Mobile-derived Human Movements and Disease Connectivitymentioning
confidence: 99%
“…The pathogens introduced by travellers may lead to secondary transmission and local outbreaks, as has been observed in severe acute respiratory syndrome, influenza, Ebola, Zika, yellow fever and measles, among others, or to the appearance of diseases such as malaria in non-endemic areas following migration for work or travel to visit friends and relatives. [3][4][5][6][7][8][9][10][11][12][13] The spread of infectious diseases and their potential health risk in travellers has resulted in substantial concerns and challenges to global health systems and economies, [14][15][16][17] with a need to place more emphasis on understanding population mobility, infectious disease connectivity and the individual health risk of travellers.…”
Section: Introductionmentioning
confidence: 99%
“…The international spread of infectious diseases including Plasmodium falciparum malaria has been accelerated by increasing human mobility via air travel over recent decades123. With many countries moving towards national malaria elimination, global eradication has risen up the international agenda45.…”
mentioning
confidence: 99%